Metode Muḥāḍarah dalam Meningkatkan Kemampuan Berbicara Bahasa Arab Santri - Maimun, Muhamad Fadhlullah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This study aims to analyze the impact of Muḥāḍarah on the Arabic-speaking skills of students at Pondok Pesantren Subulussalam Kresek. The researcher used a qualitative method to conduct direct observations and in-depth interviews with students. The study involved 145 students, with a purposive sample of 30 active students selected for participation. Data were gathered through observations and interviews and analyzed using thematic analysis. The findings indicate that Muḥāḍarah has a significant positive effect on improving students' speaking skills in Arabic. The method enhanced vocabulary, improved grammar usage, and increased students' self-confidence in speaking Arabic. Muḥāḍarah also contributed to developing students' interpersonal skills and the ability to communicate more effectively in Arabic. Furthermore, it was found to help students become more fluent and comfortable in expressing themselves in the language. The research concludes that Muḥāḍarah effectively improves Arabic speaking skills among students at Pondok Pesantren Subulussalam Kresek. This method not only aids in language acquisition but also builds confidence, making students more proficient in using Arabic in daily communication. The study recommends that Muḥāḍarah should continue to be integrated into Arabic language learning at pesantren institutions, as it plays a key role in enhancing students’ overall speaking abilities.